Preparation method of high corona voltage enameled wire
Patent Information
- Application Number
- CN202310696416.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-06-13
AI Technical Summary
但是这种方法依旧存在制约因素,一方面纳米填料的引入会直接降低材料的击穿场强,另外纳米填料具有表面能高、易团聚的特点,在电磁线上分散性差,光滑度差,直接表现在耐电晕测试中值上时好时坏,给电机的使用过程带来隐患
(1)本发明合成一种三维结构呈球形的超支化聚酯,作为低介电改性剂,通过调整超支化聚酯的含量,构建介电常数呈梯度分布的低介电绝缘漆,将该呈梯度分布的低介电绝缘漆作为漆包线的内层降低内部电场电压,有效解决了由于外侧包覆的非线性层带来的表面电位降低而导致内部电场升高的问题,实现了材料耐电压强度和防电晕性兼得的目的,继而保证了使用的安全性与稳定性。
Smart Images

Figure CN116665988B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing high corona induction voltage enameled wire, belonging to the field of wire and cable technology. Background Technology
[0002] With the popularization of new energy vehicles, research on functional components of new energy vehicles is becoming increasingly important. As a core component of new energy vehicles, drive motors are constantly developing towards higher power density and higher electromechanical efficiency in order to improve the vehicle's power and economy within a limited volume. This places increasingly higher demands on the performance of insulation materials used in motors. With the widespread application of third-generation wide-bandgap semiconductors, the operating voltage and frequency of drive motors in new energy vehicles have increased. This makes the enameled wires that carry high voltage more susceptible to phenomena such as partial discharge and corona discharge, which can severely damage the motor insulation system and accelerate the aging of the motor insulation structure. Therefore, improving the performance of enameled wires from the perspectives of corona resistance or corona prevention can significantly extend the service life of drive motors.
[0003] There are generally two methods to improve the corona resistance of motor windings: The first method focuses on structural optimization, which involves optimizing winding dimensions and varnish thickness to increase insulation thickness and reduce curvature, thereby suppressing corona generation. However, increasing thickness inevitably reduces slot fill factor and heat dissipation performance, which does not meet the actual needs of new energy vehicle motors to reduce size and increase power density. The second method focuses on material modification, which directly improves the corona resistance of the winding varnish by optimizing material formulation and processes. This method of improving corona resistance through material modification has received widespread attention both domestically and internationally. Among these methods, researchers generally believe that the introduction of nanofillers can regulate the dielectric and electrical resistance properties of materials, especially in terms of anti-corona, anti-electrical treeing, and suppression of space charge, showing a significant improvement effect, which has been verified in the market. However, this method still has limitations. On the one hand, the introduction of nanofillers directly reduces the breakdown field strength of the material. On the other hand, nanofillers have high surface energy and are prone to aggregation, resulting in poor dispersion and smoothness on electromagnetic wires. This directly manifests as inconsistent values in corona resistance tests, posing potential risks to the motor's operation. Summary of the Invention
[0004] To address the aforementioned problems in the prior art, this invention provides a method for preparing high corona initiation voltage enameled wire.
[0005] One objective of this invention is to provide a corona-resistant enameled wire, which consists of a metal core, an inner layer, and a nonlinear layer from the inside out. The inner layer is a hyperbranched polyester / epoxy insulating varnish layer, and the nonlinear layer is a modified epoxy resin shielding varnish layer.
[0006] Further specified, the inner layer is composed of 5 layers of hyperbranched polyester / epoxy insulating varnish, each layer being 0.02mm thick.
[0007] Further specified, the hyperbranched polyester content is different between adjacent hyperbranched polyester / epoxy insulating varnish layers, and the mass of hyperbranched polyester contained in the 5 hyperbranched polyester / epoxy insulating varnish layers from the inside to the outside is 7.5wt%, 5wt%, 2.5wt%, 0wt%, and 10wt% of the epoxy resin matrix, respectively.
[0008] To further define, the hyperbranched polyester / epoxy insulating varnish layer is obtained by curing an insulating varnish liquid composed of hyperbranched polyester, epoxy resin matrix, CTBN, curing agent and solvent.
[0009] Further specified, the epoxy resin matrix includes epoxy E12, epoxy E42 and CTBN, the mass ratio of epoxy E12 to epoxy E42 is 4:1, the amount of CTBN added is 15wt% of epoxy E12; the curing agent is dicyandiamide, and the amount added is 2.5wt% of epoxy resin matrix.
[0010] Further specified, the nonlinear layer thickness is 0.005mm, and the modified epoxy resin shielding coating is obtained by curing a shielding coating liquid composed of KH550-GO, epoxy resin matrix and solvent.
[0011] Further specifying, KH550-GO is oxidized GO modified with KH550, and the epoxy resin matrix is composed of epoxy E12 and epoxy E42 in a mass ratio of 4:1.
[0012] Further specified, the amount of KH550-GO added is 0.3 wt% or 0.4 wt% of the epoxy resin matrix.
[0013] Further specified, the metal core wire is made of copper and has a diameter of 1mm.
[0014] The second objective of this invention is to provide a method for preparing the above-mentioned corona-resistant enameled wire. Specifically, a multi-coating method is used to sequentially coat the surface of the metal core wire with hyperbranched polyester / epoxy insulating varnishes of different hyperbranched polyester contents, coating one layer and curing the next to obtain an inner layer; then, a nonlinear layer is coated on the surface of the inner layer.
[0015] A third objective of this invention is to provide an application of the aforementioned corona-resistant enameled wire, specifically for the manufacture of drive motors.
[0016] This invention employs a design concept that reduces the surface potential and voltage division of enameled wire to prepare it. The enameling process often utilizes a multi-layer coating process with thin layers and multiple passes, which provides feasibility for adjusting the electric field distribution of the dielectric based on combinations of materials with different dielectric constants. Taking a coaxial cylindrical electrode model as an example, at the same voltage level, increasing the dielectric constant of the outer layer material can reduce the voltage division of the outermost layer, thereby suppressing corona discharge. However, reducing the outer voltage division leads to an increase in the inner voltage division, increasing the risk of internal material breakdown and accelerating electrical aging. Therefore, it is necessary to use dielectrics with different dielectric constants to homogenize the internal electric field. This invention utilizes an insulation structure with a non-uniform distribution of dielectric parameters in a dielectric-elastic material to regulate the distribution of dielectric properties of the insulation material, thereby achieving a homogenized electric field distribution and alleviating the phenomenon of excessively high local electric fields. Simultaneously, a high-dielectric insulating varnish is used as the outer layer structure to reduce the external electric field strength and improve the degree of electric field homogenization, resulting in an enameled wire insulation structure with high dielectric strength while suppressing corona discharge. Furthermore, this invention has the following advantages compared to existing technologies: (1) This invention synthesizes a three-dimensional spherical hyperbranched polyester as a low dielectric modifier. By adjusting the content of hyperbranched polyester, a low dielectric insulating varnish with a gradient dielectric constant is constructed. This gradient low dielectric insulating varnish is used as the inner layer of the enameled wire to reduce the internal electric field voltage. This effectively solves the problem of the internal electric field increase caused by the decrease in surface potential due to the nonlinear layer on the outside. It achieves the goal of both the voltage withstand strength and anti-corona properties of the material, thereby ensuring the safety and stability of use.
[0017] (2) In this invention, KH550 is modified GO as a high dielectric filler to synthesize a high dielectric insulating varnish, which is then used as a nonlinear layer to coat the inner and outer sides of the enameled wire, thereby reducing the external electric field strength and correspondingly reducing the risk of corona generation. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the enameled wire structure provided by the present invention; Figure 2 FT-IR images of hyperbranched polyester and hyperbranched polyester / epoxy cured products; Figure 3 For hyperbranched polyester 13 C-NMR spectrum; Figure 4 Low dielectric insulating varnishes with different hyperbranched polyester contents cured at 10-10 7 A comparison chart of dielectric properties at Hz frequency; Figure 5 The breakdown field strength of low dielectric insulating varnishes cured with different hyperbranched polyester contents; Figure 6 FT-IR plots of GO and KH550-GO; Figure 7 High-resolution C1s image of XPS for GO and KH550-GO; Figure 8 High dielectric insulating varnishes with different KH550-GO contents cured at 10-10 7 A comparison chart of dielectric properties at Hz frequency; Figure 9 The breakdown field strength of low dielectric insulating varnish cured products with different KH550-GO contents. Detailed Implementation
[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0020] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0022] Example 1 like Figure 1 As shown, the enameled wire provided in this embodiment consists of a metal core wire, an inner layer, a nonlinear layer, and an air domain from the inside out. The inner layer is a hyperbranched polyester / epoxy insulating varnish layer, and the nonlinear layer is a modified epoxy resin shielding varnish layer.
[0023] The metal core is made of copper with a diameter of 1 mm; the air gap thickness is 0.02 mm. The inner layer consists of five layers of hyperbranched polyester / epoxy insulating varnish, each with a thickness of 0.02 mm. The mass of hyperbranched polyester in the five layers of hyperbranched polyester / epoxy insulating varnish, from the inside out, is 7.5 wt%, 5 wt%, 2.5 wt%, 0 wt%, and 10 wt% of the epoxy resin matrix, respectively. The nonlinear layer thickness is 0.005 mm.
[0024] The preparation method of the above enameled wire is as follows: (1) Synthesis of hyperbranched polyester: Using 1 wt.% p-toluenesulfonic acid (PTSA) as a catalyst, pentaerythritol and dimethylolpropionic acid were added to a three-necked flask at a molar ratio of 1:4, along with 1 wt% hydroquinone. The mixture was heated to 135°C and maintained for 2 hours, followed by evacuation for 0.5 hours. Then, decanoic acid and 1 wt% p-toluenesulfonic acid were added to the three-necked flask at a molar ratio of pentaerythritol:decanoic acid of 1:4. The reaction was continued at 135°C for 3 hours, followed by evacuation at 0.08 MPa for 1 hour to reduce the acid value to below 20 mg KOH / g, yielding a hyperbranched polyester, which was used as a low-dielectric modifier.
[0025] The synthesized hyperbranched polyester was characterized by FT-IR, and the results are as follows: Figure 2 The HBP curve is shown in the figure.
[0026] The degree of branching of the synthesized hyperbranched polyester was characterized. 13 C-NMR spectrum as shown Figure 3 As shown, by Figure 3 It can be seen that the "T" structure peak appears around 49.76 ppm, representing the uncapped terminal units of the hyperbranched polyester; the "L" structure peak appears around 48.71 ppm, indicating that half of the hydroxyl groups at the end of the hyperbranched polyester are grafted with n-decanoic acid, while the other half are not grafted; the "D" structure peak appears around 46.65 ppm, indicating that all the hydroxyl groups at the end of the hyperbranched polyester are grafted with n-decanoic acid. Defining the area of the "L" structure peak as 1, the area of the "T" structure peak is 0.11, and the area of the "D" structure peak is 0.7. Therefore, the degree of branching of the hyperbranched polyester can be calculated using the following formula:
[0027] Calculations show that DB 超支化聚酯 =0.45, which indicates that when pentaerythritol and n-decanoic acid are capped at a molar ratio of 1:4, the majority of the ends appear as "L" and "D" structures, resulting in the synthesis of hyperbranched polyesters with a high degree of branching.
[0028] (2) Preparation of low-dielectric paint: Solid epoxy resin E12 was dissolved in xylene and n-butanol, and then polyurethane modified epoxy resin E42 was added. The mass ratio of epoxy E12 to epoxy E42 was 4:1. Then, 15 wt% of carboxyl-terminated butadiene-acrylonitrile rubber CTBN of epoxy E12 was added. The mixture was stirred at 90°C for 4 hours to obtain the epoxy resin matrix.
[0029] A series of low-dielectric insulating varnishes were prepared by thoroughly mixing epoxy resin matrix with different contents of hyperbranched polyester (0 wt.%, 2.5 wt.%, 5 wt.%, 7.5 wt.%, 10 wt.%) of epoxy resin, and mixing in dicyandiamide (2.5 wt.%) as a curing agent dissolved in DMF.
[0030] The low-dielectric insulating varnish was placed in a vacuum oven and vacuumed for 1 hour to remove bubbles. It was then coated on the surface of the copper sheet and the copper wire. The varnish was then cured by holding it at 120°C for 1 hour, 140°C for 1 hour, and 160°C for 1 hour to obtain the test sample.
[0031] FT-IR characterization of hyperbranched polyester / epoxy cured products yielded the following results: Figure 2 As shown, by Figure 2 It can be seen from the spectrum of the hyperbranched polyester HBP that the 3350 cm⁻¹ line belongs to -OH. -1 The peak has essentially disappeared, and it is also at 1380 cm⁻¹. 1 The observation of the methyl structure peak at the alkyl acid terminus proves that n-decanoic acid, as a capping agent, has been completely grafted into the hyperbranched polyester, whereas the 3350 cm⁻¹ peak in pure epoxy resin and hyperbranched polyester / epoxy cured product... -1 It's the -OH group inherent in epoxy resin; 1730cm -1 and 1150cm -1 It is a characteristic peak of C=O, 1008 cm⁻¹ 1 The peak at 908 cm⁻¹ is caused by the vibration of CO. The figure shows that the hyperbranched polyester / epoxy cured material exhibits a peak at 908 cm⁻¹. -1 The disappearance of the characteristic peaks of the nearby epoxy groups indicates that the epoxy insulating varnish has been completely cured.
[0032] The test samples with different hyperbranched polyester contents obtained above were subjected to a concentration of 10-10... 7 Dielectric properties were characterized at a frequency of Hz, and the specific results are as follows: Figure 4 As shown, by Figure 4It can be seen that with the increase of hyperbranched polyester doping content, the dielectric constant of the insulating varnish first decreases and then increases. When the hyperbranched polyester doping content is 7.5 wt%, the dielectric constant of the insulating varnish is the smallest, which is 4.15 at the power frequency of 50 Hz. This is because the spherical three-dimensional structure of hyperbranched polyester increases the free volume of the insulating varnish, thereby reducing the number of polar groups per unit volume, which macroscopically manifests as a decreasing trend in dielectric constant. As the hyperbranched polyester content increases, the increase in free volume gradually approaches saturation, and uncapped polar groups are introduced, leading to an increase in the dielectric constant of the insulating varnish. Therefore, different contents of hyperbranched polyester have different abilities to reduce the dielectric constant of the insulating varnish. Thus, using different contents of hyperbranched polyester as dielectric modifiers for epoxy resins can yield a series of insulating varnishes with different dielectric constants. Furthermore, the dielectric constant of all insulating varnishes decreases with increasing frequency. This is because, due to steric hindrance and interactions between molecular chains, molecules with large electric dipole moments cannot keep up with the frequency changes as the test frequency increases. Only a small number of polar molecules can maintain a decreasing dielectric constant as the electric field changes. In addition, the dielectric loss of the insulating varnish first decreases and then increases with increasing hyperbranched polyester doping content, reaching its minimum at 7.5 wt% hyperbranched polyester doping. Because hyperbranched polyester has numerous flexible segments at its ends, it can physically entangle with epoxy resin segments, forming an interpenetrating network structure. This restricts the vibration of free segments and detached segments in the resin system, causing some vibration to cancel or decrease, thus reducing the dielectric loss of the insulating varnish. However, excessive addition of hyperbranched polyester significantly increases the content of flexible segments in the system, leading to an increase in free segments per unit volume and thus increasing the dielectric loss of the insulating varnish.
[0033] The breakdown strength of the test samples with different hyperbranched polyester contents obtained above was tested, and the Weibull distribution of the breakdown strength was plotted. The results are as follows: Figure 5 As shown, by Figure 5 It can be seen that when the amount of hyperbranched polyester added is less than 7.5 wt%, the breakdown strength of the insulating varnish increases with the increase of the hyperbranched polyester content. When the hyperbranched polyester content is 7.5 wt%, the characteristic breakdown field strength of the insulating varnish reaches 51.7 kV·mm. -1The breakdown strength is 54.3% higher than that of pure epoxy resin varnish. This is due to the addition of hyperbranched polyester, whose longer flexible segments intertwine with the epoxy resin segments, resulting in a denser structure that restricts the movement of free electrons. Simultaneously, the introduction of a small amount of hyperbranched polyester, due to its unique molecular structure, can eliminate some internal defects in the epoxy resin, all of which improve the overall breakdown performance of the insulating varnish. However, excessive hyperbranched polyester can hinder the curing of the epoxy resin, reduce the crosslinking density, and the large number of spherical structures makes the epoxy molecules loose, making it difficult to form a dense structure. This can introduce new defects, leading to a decrease in the breakdown field strength.
[0034] (3) Preparation of KH550 modified GO Add oxidized GO to anhydrous ethanol, stir evenly and sonicate for 30 min, add KH550 dropwise, continue sonication for 30 min, react at 80℃ for 24 h after sonication, finally wash with anhydrous ethanol by centrifugation several times, and dry to obtain KH550-GO.
[0035] FT-IR analysis was performed on GO and KH550 modified GO, and the results are as follows: Figure 6 As shown in the figure, the KH550-GO curve is at 1540 cm⁻¹. -1 A distinct -NH bending vibration absorption peak appeared at 2924 cm⁻¹, confirming the formation of the amide bond. -1 and 2858cm -1 These are the characteristic absorption peaks of the methyl and methylene groups on the silane coupling agent, with a wavenumber of 1108 cm⁻¹. -1 and 1030 cm -1 The peaks at these locations represent the characteristic absorption peaks of -Si-O-Si- and -Si-OC, respectively, which all indicate that KH550 has been successfully grafted onto the GO surface.
[0036] Semi-quantitative analysis of chemical bond changes in KH550-grafted GO using XPS, such as... Figure 7 As shown, the GO spectrum exhibits three prominent peaks at binding energies of 284.6 eV, 286.6 eV, and 288.4 eV. These represent the CC and C=C bonds on the unoxidized carbon skeleton, the terminal hydroxyl C-OH and COC epoxy rings on the GO surface, and the terminal carboxyl OC=O group on the GO surface, respectively. In KH550-GO, the binding energy of the prominent peak at 286.6 eV, representing the GO hydroxyl and epoxy groups, remained essentially unchanged, but the peak height and width decreased significantly. Furthermore, the peak height of OC=O decreased significantly, and a new CN peak appeared at a binding energy of 285.6 eV. These characteristics indicate that KH550 reacted with the epoxy and carboxyl groups on the GO surface, successfully grafting them onto GO.
[0037] (4) Preparation of high dielectric paint KH550-GO (0 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt% of epoxy resin) was added to DMF and ultrasonically stirred for 0.5 h. Then it was added to the above epoxy resin matrix, and DICY (2.5 wt% of epoxy resin) was dissolved in DMF and mixed in. After thorough stirring, a series of high dielectric insulating varnishes were obtained.
[0038] The high-dielectric insulating varnish was placed in a vacuum oven and vacuumed for 1 hour to remove bubbles. It was then coated on the surface of the copper sheet and the copper wire. The varnish was then cured by holding it at 120°C for 1 hour, 140°C for 1 hour, and 160°C for 1 hour to obtain the test sample.
[0039] The test samples with different KH550-GO contents obtained above were subjected to a 10-10 7 Dielectric properties were characterized at a frequency of Hz, and the results are as follows: Figure 8 As shown. Under the influence of an alternating electric field, the factors affecting the dielectric constant of graphene insulating varnish are interfacial polarization and directional polarization. Among them, interfacial polarization mainly acts at low frequencies. Figure 8It is known that at low frequencies, the dielectric constant of KH550-GO insulating varnish is directly proportional to the amount of KH550-GO added. This is because as the amount of KH550-GO added increases, the number of polar groups increases, the interfacial polarization becomes more pronounced, and the relative dielectric constant increases accordingly. Simultaneously, with the addition of graphene, its sheet structure, when uniformly dispersed in epoxy resin, can form individual microcapacitors. As the amount of graphene added increases, the number of effective microcapacitors formed in the system increases, and the number of effective polarized interfaces between the two phases increases, further increasing the dielectric constant. However, when the frequency of the alternating electric field increases, the electric field frequency becomes too fast, much greater than the change in charge, and the effect of the most significant influencing factor, interfacial polarization, decreases accordingly. Therefore, the dielectric constant of the insulating varnish with the same amount of added GO decreases in the high-frequency region. However, due to the introduction of new polar groups, the dielectric constant of the varnish with added GO is still higher than that without added GO. Furthermore, excessive GO surfaces attract and aggregate, leading to interfacial region superposition when added to the matrix. This restricts directional polarization, resulting in a decrease in dielectric constant at high frequencies for KH550-GO / EP insulating varnish with 0.5 wt% addition compared to 0.3 wt% and 0.4 wt% addition. In addition, the dielectric loss factor of KH550-GO / EP insulating varnish is directly proportional to the amount of KH550-GO added. As the amount of KH550-GO increases, more interfaces are formed between it and the epoxy resin matrix, resulting in more effective interfaces and a more pronounced interfacial loss effect caused by interfacial polarization. Simultaneously, this interfacial polarization loss decreases rapidly with increasing frequency. Moreover, since graphene is a conductive filler, increasing its addition shortens the distance between GO particles, generating leakage current under an alternating electric field, causing leakage loss and further increasing dielectric loss.
[0040] The breakdown strength of the test samples with different KH550-GO contents obtained above was tested, and the Weibull distribution of the breakdown strength was plotted. The results are as follows: Figure 9 As shown, by Figure 9 It can be seen that the breakdown voltage first increases and then decreases with the increase of KH550-GO content. When the KH550-GO content is 0.3 wt.%, the characteristic breakdown voltage of the insulating varnish can reach 41 kV·mm-1, which is 22.4% higher than that of pure epoxy varnish. However, when the content is further increased, the breakdown field strength begins to decrease significantly. This is because KH550-GO has a high aspect ratio sheet structure. The KH550-GO dispersed in the epoxy matrix comes into contact with the epoxy, which can form a large number of microcapacitors, causing low-energy electrons to be trapped and restricting the conduction of some electrons in the matrix, resulting in an increase in the breakdown field strength. However, as the KH550-GO content increases, the GO sheet structure begins to come into contact with each other, and electrons are more easily transferred between the graphene sheets. Conductive pathways are gradually formed, and the breakdown field strength of the insulating varnish decreases significantly.
[0041] (5) Preparation of enameled wire A multi-coating method was used to sequentially coat the surface of the metal core wire with hyperbranched polyester / epoxy insulating varnishes of varying hyperbranched polyester content. The coating sequence of the hyperbranched polyester / epoxy insulating varnishes was 7.5wt%, 5wt%, 2.5wt%, 0wt%, and 10wt% of the epoxy resin matrix, with each layer being 0.02mm thick. Each layer was coated and cured sequentially under the following curing conditions: 120℃ for 1 hour, 140℃ for 1 hour, and 160℃ for 1 hour, resulting in the inner layer. Then, a nonlinear layer with a thickness of 0.005mm was coated onto the inner layer using a high-dielectric varnish with KH550-GO added at 0.4 wt.%. After coating, the layer was cured under the following curing conditions: 120℃ for 1 hour, 140℃ for 1 hour, and 160℃ for 1 hour, resulting in the nonlinear layer.
[0042] Example 2: The difference between this embodiment and embodiment 1 is that (5) a high dielectric varnish with an addition amount of 0.3 wt.% of KH550-GO is used to prepare the enameled wire.
[0043] Using Comsol Multiphysics simulation software, the effects of different dielectric gradient structures on the electric field distribution of the overall insulation structure, as well as the influence of the nonlinear layer material on the electric field, were analyzed by combining the aforementioned low-dielectric insulating varnishes into structures with different dielectric gradients. The electric field distribution of the overall insulation structure was plotted to verify that the low-dielectric varnish prepared in Example 1 possesses high dielectric strength and anti-corona properties. The results are as follows: (1) Using KGO insulating varnish as the nonlinear shielding outer coating can significantly reduce the outer electric field. At the same thickness, the potential at the potential inflection point decreases with the increase of KGO content (0 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%). When the thickness is 0.02 mm, the voltage drops from 270 V in pure insulating varnish to 254 V, 213 V, 53 V, and 52 V, respectively, representing decreases of 6%, 21%, 80%, and 81%. In terms of electric field distribution, the degree of decrease in electric field also increases with the increase of KGO content. The effect is most obvious when the KGO content is 0.4 wt.% KGO / epoxy varnish. The electric field on the surface of the insulating layer near the air side is less than the air breakdown electric field (3 kV / mm), which is 80.6% lower than the outermost surface electric field when using pure insulating varnish.
[0044] (2) Further dielectric constant insulation structure is constructed in the inner layer. After the dielectric constant of the innermost layer near the copper core is gradually reduced from 5.6 to 4.1, the electric field strength it shares is reduced from 17.26 kV·mm. -1 Reduced to 14.66 kV·mm -1 This represents a 15.1% decrease. Meanwhile, the field strength in the inner layer near the nonlinear layer decreased from 15.70 kV·mm.-1 Increased to 18.54 kV·mm -1 When the dielectric constant of the adjacent media is further reduced, the maximum and minimum electric field strengths of each layer in the inner layer remain at 16.7 kV·mm. -1 and 16.4kV·mm -1 Nearby, the electric field difference between adjacent paint layers decreased to 0.3 kV·mm. -1 The reduction in the electric field strength difference between adjacent paint layers indicates that the electric field strength distribution has been further homogenized.
[0045] In summary, the enameled wire structure provided in Example 1 is a feasible means to suppress corona discharge.
[0046] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.
Claims
1. A high corona induction voltage enameled wire, characterized in that, From the inside out, the layers are a metal core wire, an inner layer, and a nonlinear layer. The inner layer is a hyperbranched polyester / epoxy insulating varnish layer, and the nonlinear layer is a modified epoxy resin shielding varnish layer. The inner layer is composed of five layers of hyperbranched polyester / epoxy insulating varnish, each layer being 0.02 mm thick. The hyperbranched polyester content varies between adjacent hyperbranched polyester / epoxy insulating varnish layers. The mass of hyperbranched polyester contained in the five hyperbranched polyester / epoxy insulating varnish layers from the inside out is 7.5 wt%, 5 wt%, 2.5 wt%, 0 wt%, and 10 wt% of the epoxy resin matrix, respectively. The nonlinear layer has a thickness of 0.005 mm. The modified epoxy resin shielding coating is obtained by curing a shielding coating liquid composed of KH550-GO, epoxy resin matrix, DICY and solvent.
2. The high corona induction voltage enameled wire according to claim 1, characterized in that, The hyperbranched polyester / epoxy insulating varnish layer is obtained by curing an insulating varnish liquid composed of hyperbranched polyester, epoxy resin matrix, CTBN, curing agent and solvent.
3. The high corona induction voltage enameled wire according to claim 2, characterized in that, The epoxy resin matrix includes epoxy E12, epoxy E42 and CTBN, with the mass ratio of epoxy E12 to epoxy E42 being 4:1, and the amount of CTBN added being 15 wt% of epoxy E12; the curing agent is dicyandiamide, and the amount added is 2.5 wt% of the epoxy resin matrix.
4. The high corona induction voltage enameled wire according to claim 1, characterized in that, KH550-GO is a GO modified using KH550.
5. The high corona induction voltage enameled wire according to claim 1, characterized in that, The amount of KH550-GO added is 0.3 wt% or 0.4 wt% of the epoxy resin matrix, and the amount of DICY added is 2.5 wt% of the epoxy resin matrix.
6. A method for preparing a high corona initiation voltage enameled wire according to any one of claims 1-5, characterized in that, A multi-coating method is used to sequentially coat the surface of the metal core wire with hyperbranched polyester / epoxy insulating varnishes of different hyperbranched polyester contents, with each layer being coated and cured to obtain the inner layer; then a nonlinear layer is coated on the surface of the inner layer.
7. An application of the high corona initiation voltage enameled wire according to any one of claims 1-5, characterized in that, Used to drive motors.
Citation Information
Patent Citations
Method for making of polymer high voltage electric insulators
BG105990A
Method of making an insulated conductive component
EP3940120A1